Peran Pustakawan dalam Pendampingan Penggunaan Media Sosial Terhadap Perilaku Remaja di Masyarakat - Maniso Mustar (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
Introduction. Information and communication technology develops very rapidly. Without exception, social media thrives in all circles including teenagers. Social media gives benefits in life and able to provide positive impacts in economic, social and cultural. However, in the midst of the widespread use of social media, sometimes users are not aware of the negative impacts such as social media influences towards teenagers behaviours. This article aims to assist teenagers in controlling behavior due to the influence of social media in society. Methodology. This research use descriptive method. Data collection and analysis was done with literature review from various references. Results and Discussion. This research show that social media influences teenagers’ behavior by bridging activites and friendship which may bring positive and negative impacts. Librarians may have roles in social media by giving positive values through providing constructive information which has value economically, culturally and socially among teenagers and wider community. Conclusion. Librarians can help the community by giving accompaniment in social media usage and shaping teenagers characters through attitudes, patriotic behavior, upholding democracy and towards civil society that applies knowledge responsibly towards humanity through planned programs.